(untitled) (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2017)
The text tells the geographic-cartographic history of the trajectory of Prof. Dr. Rafael Sanzio Aaraújo dos Anjos at the time of presentation and defense of his Memorial of Full Professor, held in October 2016 at the University of Brasília. The document is structured in six parts that dialogue, in a way, between them. The first gives a retrospect of some references from my childhood-adolescence-youth; The second part deals with the training in Geography in the Institute of Geosciences of the Federal University of Bahia, the projects and stages; In the third moment of the Memorial are focused the contexts of accomplishment of the Master in Urban Planning in the FAU-UnB; The link and openings with the Department of Geography of UnB and the continuity of the research in sequence in the Program of Post-Graduation in Space Information (POLIUSP); In the following the references of the Afro-Brazilian Geography Project (GEOAFRO Project) in the country and abroad, as well as its publications, thematic exhibitions and educational programs (thematic workshops); The fifth part shows the results of researches and projects carried out by approaching their results and products with exhibitions, books, videos, workshops, articles, among other procedures that add the tripod of research, teaching and extension seeking to "talk" with Civil society and the decision-making sector using more effective languages and in the last part the focus is on the current moment and the operationalization of studies and projects.